PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VA SD NEGRI 019 SEKELADI TANAH PUTIH - Siti Muliana; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study is based on the low learning outcomes of science students of class V in SDN 019 Sekeladi Tanah Putih Academic Year 2016/2017. Preliminary data received by the researchers, from 28 students who reached the value of KKM only 5 students (20.83%) with an average of 54.37. This research is a classroom action research conducted collaboratively and participatively in collaboration with science teacher class V in SD Negeri 019 Sekeladi Tanah Putih. The instrument of this study consists of learning devices used in this study based on Education Unit Level Curriculum (KTSP). Learning tools consist of syllabus, lesson plans, student worksheets and observation sheets. The result of the research showed that teacher activity in the first cycle of meeting I was 58,33% with enough category, second meeting of cycle I was 75% with good category. At the second meeting I meeting is 83,33% with very good category and second meeting second cycle is 95,83% with very good category. Then the percentage of first cycle activity of the first student is 54,17% with enough category, at the second meeting of cycle I that is 70,833% with good category. In the second cycle of meeting I is 87.5% with very good category, and meeting II is 91.67% with very good category. The students' learning outcomes are complete before the action is held only 5 students (20.83%) with an average value of 54.37. In the daily test I cycle I the number of completed students increased to 11 students or (45.83%) with an average score of 66.04. Furthermore, in the second cycle II repetition increased again with a total number of students who completed 22 students or (91.67%) with an average score of 83.33. The increase in student learning outcomes between the baseline score of one cycle with an average of 21.45% and between the basic score of the second cycle with an average of 53.26%. This means that the classical value obtained by students has above KKM has been determined.Keywords: Inquiry Learning Model, Learning Outcomes IPA